#### Answer

True

#### Work Step by Step

Substituting $x=2$ in $f(x)=-x^{2}-1$ and then simplifying, we obtain:
$f(x)=-x^{2}-1$
$f(2)=-(2)^{2}-1$
$f(2)=-4-1$
$f(2)=-5$
Therefore, the statement is true.

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

True

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.